Bitcoin:Surveying First Revolutionary Cryptographic Virtual Currency - Nasti, SM; Nasti, SJ; Bashir, R; Butt, MA (International Journal of Computer Sciences and Engineering, 2025)
Bitcoin - a new virtual currency may change the world as it is the first currency which is not tied to any bank or government agency. It is also the first global currency that uses cryptography allowing users to utilize money anonymously and having full control over its saving and expenditure. Since its inception in 2009, it is still in its infancy but is gaining popularity with each passing day and might replace existing currencies in near future. Bitcoin being open source acts as a revolutionary currency for e-procurement. The aim of this paper is to explore the concept behind exchanging and trading, introduces the concept of Bitcoin and illustrates the process of Bitcoin mining.